What Does Imaging Reveal About the Pathology of Amyotrophic Lateral Sclerosis? - Turner, Martin R. (Curr Neurol Neurosci Rep, 2015)
Amyotrophic lateral sclerosis (ALS) is now recognised to be a heterogeneous neurodegenerative syndrome of the motor system and its frontotemporal cortical connections. The development and application of structural and functional imaging over the last three decades, in particular magnetic resonance imaging (MRI), has allowed traditional post mortem histopathological and emerging molecular findings in ALS to be placed in a clinical context. Cerebral grey and white matter structural MRI changes are increasingly being understood in terms of brain connectivity, providing insights into the advancing degenerative process and producing candidate biomarkers. Such markers may refine the prognostic stratification of patients and the diagnostic pathway, as well as providing an objective assessment of changes in disease activity in response to future therapeutic agents. Studies are being extended to the spinal cord, and the application of neuroimaging to unaffected carriers of highly penetrant genetic mutations linked to the development of ALS offers a unique window to the pre-symptomatic landscape.